(untitled) - Burger, Edward ([Austin, Tex.])
A digital textbook that communicates the fundamentals of college algebra using interactive multimedia. Some of the features available for the student: a series of multimedia video lectures that are adaptable to any course syllabus, interactive exercises with feedback, review materials, real-life applications, a student help center and free technical support
Keywords: Algebra,Algebra